Guide to molecular cloning techniques - Berger, Shelby L.; Kimmel, Alan R. (Methods in enzymology)
Requirements for a molecular biology laboratory. General methods for isolating and characterizing nucleic acids. Enzymatic techniques and recombinant DNA technology. Restriction enzymes. Growth and maintenance of bacteria. Genomic cloning. Preparation and characterization of RNA. Preparation of cDNA and the generation of cDNA libraries. Selection of clones from libraries. Identification and characterization of specific clones.